Analysis of Sustainable Municipal Solid Waste Management Alternatives Based on Source Separation Using the Analytic Hierarchy Process - Apaydin, Omer (MDPI, 2025)
The aim of this study is to determine the effect of the separation of solid waste at the source on three different sustainable solid waste management scenarios using the analytic hierarchy process. In this context, the type of source separation method that would be most appropriate for three solid waste management scenarios was investigated (A1: material recycling facility + sanitary landfill; A2: material recycling facility + biological processes + sanitary landfill, and A3: thermal processes + biological processes + sanitary landfill) based on well-known solid waste management alternatives. Firstly, solid waste management scenarios were determined as decision points. Secondly, three solid waste collection options at the source (mixed: there is only one type of bin for all solid waste components; binary: paper + metal + plastic + glass, kitchen organics, and others; and triple: paper + metal + plastic + glass, kitchen organics, and others) were chosen as the main criteria affecting the decision points. Thirdly, fifteen sub-criteria were chosen based on the main criteria. In the process, not only the main and sub-criteria, but also stakeholders' contributions are vital. For the pairwise comparison of all the criteria to be used in the study, the opinions of thirteen experts as stakeholders were obtained through face-to-face interviews. Within the scope of the zero waste vision, with a focus on environmental protection, the analytical hierarchy process was applied via pairwise comparisons of decision points and factors affecting the decision points. According to the results, in the case of mixed collection at the source, high preference rates were obtained for A1 as the decision point in terms of environmental (0.665), economic (0.699), social (0.510), and technical (0.544) criteria. In the case of binary separation at the source, A1 has high preference rates as the decision point in terms of environmental (0.553), economic (0.673), social (0.507), and technical (0.632) criteria. In the case of triple separation at the source, it is calculated that the A1 alternative has the highest preference values as the decision point in terms of environmental (0.558), economic (0.669), social (0.514), and technical criteria (0.611). Hence, the determining factor in the efficient integration of sustainable waste management with smart technologies is how waste is managed at the source. It is hoped that the results obtained in this study within the scope of the zero waste vision will assist decision-makers during sustainable municipal solid waste management processes.
Keywords: analytic hierarchy process; mixed-binary-triple collection processes; separation at source; sustainable waste management; zero waste; SMART CITIES; SYSTEM; AHP; Science & Technology - Other Topics; Environmental Sciences & Ecology